Simplify. (Polynomials) 1. (2cd^3)(-2c)(3c^d) =

2. (2x^2)(3x^6) - (4x^4)(2x^4) =

3. (6x^2)(3x^6) + (4x^4)(2x^4) =

4. (2ab^2)^2(-3a^2b^2) =

5. -6a^3(a^2-2a+1) =

6. -2xy(x^2-3xy+y^2) =

7. (a+b) (2a^2-ab+3b^2) =

(Please help asap!)

Answers

Answer 1
Answer: 1. (2cd^(3))(-2c)(3c^(d))=\n-12c^(d+2)d^(3)

2. (2x^(2))(3x^(6))-(4x^(4))(2x^(4))=\n6x^(8)-8x^(8)=\n-2x^(8)

3. (6x^(2))(3x^(6))+(4x^(4))(2x^(4))=\n18^(8)+8x^(8)=\n26x^(8)

4. (2ab^(2))^(2)(-3a^{2b^(2)})=\n4a^(2)b^(4)(-3a^{2b^(2)})=\n-12a^{2b^(2)+2}b^(4)

5. -6a^(3)(a^(2)-2a+1)=\n-6a^(5)+12a^(4)-6a^(3)

6. -2xy(x^(2)-3xy+y^(2))=\n-2x^(3)y+6x^(2)y^(2)-2xy^(3)

7. (a+b)(2a^(2)-ab+3b^(2))=\n2a^(3)-a^(2)b+3ab^(2)+2a^(2)b-ab^(2)+3b^(3)=\n2a^(3)+3b^(3)+a^(2)b+2ab^(2)
Answer 2
Answer: 1.(2cd^(3))(-2c)(3cd)
   -12c^(3)d^(4)

2.(2x^(2))(3x^(6)) - (4x^(4))(2x^(4))
   6x^(8) - 8x^(8)
   -2x^(8)

3.(6x^(2))(3x^(6)) + (4x^(4))(2x^(4))
   18x^(8) + 8x^(8)
   26x^(8)

4.(2ab^(2))^(2)(-3a^(2)b^(2))
   ((2ab^(2))(2ab^(2)))(-3a^(2)b^(2))
   (4a^(2)b^(4))(-3a^(2)b^(2))
   -12a^(4)b^(6)

5.-6a^(3)(a^(2) - 2a + 1)
   -6a^(3)(a^(2)) + 6a^(3)(2a) - 6a^(3)(1)
   -6a^(5) + 12a^(4) - 6a^(3)

6.-2xy(x^(2) - 3xy + y^(2))
   -2xy(x^(2)) + 2xy(3xy) - 2xy(y^(2))
   -2x^(3)y + 6x^(2)y^(2) - 2xy^(3)

7.(a + b)(2a^(2) - ab + 3b^(2))
   (2a^(3) - a^(2)b + 3ab^(2) + 2a^(2)b - ab^(2) + 3b^(3))
   (2a^(3) - a^(2)b + 2a^(2)b + 3ab^(2) - ab^(2) + 3b^(3))
   2a^(3) + a^(2)b + 2ab^(2) + 3b^(3)
  

Related Questions

IAcellusFind the volume of the cone.5Diameter: 14 m, Slant Height: 25 mHelp ResourcesRound to the nearest whole number.Volume[?] m3
HELP!(:Find any points of discontinuity for the rational function. y= (x+6)(x+2)(x+8)/(x+9)(x+7)
M is the midpoint of YZ. If YM = x + 3, and YZ = 3x -1, find MZ
What is the correct classification of 23x + 16?
Factor the expression completely 6x^2 + 21x - 12​

I NEED HELP ASAP!!!Question: Which equation applies the associative property of multiplication?

Answers

i’m not 100% but from what i know i think it’s (C.)

what is the solution to the system of equations? y =1/3 x – 10 2x y = 4 (–8, 6) (–6, 16) (6, –8) (16, –6)

Answers

Answer:

Option C is correct.

Solution to the given system of equation is (6 , -8)

Step-by-step explanation:

Given the system of equation:

y= (1)/(3) x-10             ......[1]

2x+y =4                           .....[2]

Substitute the equation [1] in [2] we get;

2x +(1)/(3)x -10 =4

Combine like terms;

(7)/(3)x -10 =4

Add 10 to both side of an equation:

(7)/(3)x -10 +10=4+10

Simplify:

(7)/(3)x =14

Divide both sides by  (3)/(7) we get;

(3)/(7) * (7)/(3)x = 14 * (3)/(7)

Simplify:

x = 6

Substitute the value of x =6 in equation [1] we get;

y= (1)/(3)(6)-10

or

y= 2-10  

Simplify:

y = - 8

therefore, the solution to the given system of equation is; (6 , -8)

You can also see in the graph as shown below:

y = 1/3 x - 10
2x + y = 4
2x + 1/3 x - 10 = 4
7/3 x = 14
x = 6
y = 1/3(6) - 10 = 2 - 10 = -8
Therefore solution is (6, -8)

Nicole deposited $2,000 at 6% simple interest. How long will it be before she has $2,600 in her account?

Answers

\bf \qquad \textit{Simple Interest Earned Amount}\n\nA=P(1+rt)\qquad \begin{cases}A=\textit{accumulated amount}\to &2,600\nP=\textit{original amount deposited}\to& \$2,000\nr=rate\to 6\%\to (6)/(100)\to &0.06\nt=years\end{cases}

solve for "t"

One of the three main questions of economics addresses who should

Answers

Here are the Three Main Economic Questions
1) Who consumes the goods and services produced in society?
2) What goods and services must be produced in society?
3) How should goods and services be produced in society?

These questions are very important because it deals on how available resources are allocated to produce essential goods and services demanded by consumers. 

Answer:

C, receive goods and services.

Step-by-step explanation:

What is 20% off of £1.85? ^_^

Answers

p\%=(p)/(100)\n\n20\%=(20)/(100)=0.2\n\n20\%\ of\ \£1.85\ is\ 0.2\ *\ \£1.85=\£0.37
 £1.85 ________ 100 %
       x ________ 20 %

100x = 20 . 1,85
100x = 37
x = 37 / 100
x = 0,37

is 
 £0,37 ! 

Elia rode her bicycle from her house to the beach at a constant speed of 18 kilometres per hour and then rode from the beach to the park at a constant speed of 15 kilometres per hour. The total duration of the rides was 1 hour and the distances she rode in each direction are equal. Let b be the number of hours it took Elia to ride from her house to the beach, and p the number of hours it took her to ride from the beach to the park.

Which system of equations represents this situation?

Answers

Answer:

I'm sorry but I don't see any equations

Step-by-step explanation: